Memudarnya Pengetahuan Lokal Masyarakat tentang Pengobatan Diare di Kampung Kuin Kota Banjarmasin - Natasya Camilla; Arif Rahman Hakim (Prodi Sosiologi FISIP ULM, 2023)
The ignorance of the people of Kampung Kuin in treating diarrhea is a big problem and disturbing because it has claimed victims. This research aims to find out how local knowledge owned by the people of Kampung Kuin in treating diarrhea, as well as the factors that make people begin to forget the local knowledge. This research uses qualitative research methods, narrative approach. Data collection used interviews, observation and documentation. This research is located in Gang Hikmah RT. 08 Kampung Kuin, North Kuin Village, West Banjarmasin Subdistrict, Banjarmasin City. The data analysis technique used the Miles and Huberman model. The results showed that the people of Kuin village can tell and can explain local knowledge about diarrhea treatment directly. The knowledge that the community has is not only used for themselves, but is disseminated to relatives and neighbors to use village medicine that must still exist in this modern era. Traditional plants are still known even though they have been lost due to development in land settlements. The development of small lanes on land has caused the loss of nutritious plants. Pharmacies that have sprung up in land settlements have made the Kuin Village community group that purely uses village medicine begin to decrease, most of the community has moved to modern drugs that are more practical. Differences in the environment and daily habits of the Kuin Village community distinguish people who still use village medicine from those who use modern medicine.